2006
DOI: 10.1161/01.hyp.0000229668.73501.e8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Saturated Fat and Linolenic Acid on the Association Between Intake of Dairy Products and Blood Pressure

Abstract: Abstract-Data on the association between dairy consumption and blood pressure have been inconsistent. We sought to examine the relation between dairy consumption and prevalent hypertension (HTN) among 4797 participants of the National Heart, Lung, and Blood Institute Family Heart Study. We used generalized estimating equations to estimate prevalence odds ratios of HTN across categories of dairy consumption. From the lowest to the highest sex-, age-, and energy-adjusted quartile of dairy consumption, there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
3
27
0
2
Order By: Relevance
“…The association between dairy product intake and BP, hypertension have been examined more in cross-sectional studies [21][22][23][24] than in prospective studies. 8 -10 The Framingham Children's Study found that children who consumed 2 or more servings/d dairy products during preschool years had smaller SBP gain throughout childhood and lower SBP by early adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…The association between dairy product intake and BP, hypertension have been examined more in cross-sectional studies [21][22][23][24] than in prospective studies. 8 -10 The Framingham Children's Study found that children who consumed 2 or more servings/d dairy products during preschool years had smaller SBP gain throughout childhood and lower SBP by early adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…(51) , women; ( ), Abbott et al (57) ; ( ), Engberink et al (59) ; ( ), Djousse et al (212) ; ( ), Liu et al (55) ; ( ), Umesawa et al (63) men; ( ), Umesawa et al (63) women; ( ), Alonso et al (58) ; ( ), Wang et al (213) ; ( ), Mirmiran et al (24) men; ( ), Mirmiran et al (24) women; ( ), Murakami et al (26) ; ( ), Snijder et al (29) ; ( ), Liu et al…”
Section: Evidence From Intervention Trials Without Energy Restrictionmentioning
confidence: 99%
“…Também nesse estudo o efeito foi maior entre os que consumiam menos gorduras saturadas. Os autores também não encontraram evidência de interação entre ácido linolênico e consumo de derivados de leite na HA (Djousse, et al, 2006).…”
Section: Derivados Do Leiteunclassified